2016
DOI: 10.4018/irmj.2016100103
|View full text |Cite
|
Sign up to set email alerts
|

IT Project Development using Capability Maturity Model

Abstract: In many research studies on IT project development process, the authors have noticed that different frameworks are used for this purpose. In fact, many companies choose specific frameworks to run their IT projects based on project type and face dissimilar problems during the execution. In this research the authors are presenting a framework for IT project development using Capability Maturity Model. The framework has been developed to improve the IT project development in a large company because of the lower r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Nasir and Sahibuddin (2011) have categorised the critical success factors specifically for any software development team and software organisation. Since then, several other studies (Da Silva & Dos Santos, 2017;Fayaz et al, 2017;Ibrahim et al, 2013;Kabir & Rusu, 2016;Kateb et al, 2015;Sudhakar, 2016) Those 26 are not the only critical success factors that affect software development projects, however, they appear at the top of many other studies like in Chiyangwa and Mnkandla (2017).…”
Section: Summary Of Critical Success Factorsmentioning
confidence: 99%
“…Nasir and Sahibuddin (2011) have categorised the critical success factors specifically for any software development team and software organisation. Since then, several other studies (Da Silva & Dos Santos, 2017;Fayaz et al, 2017;Ibrahim et al, 2013;Kabir & Rusu, 2016;Kateb et al, 2015;Sudhakar, 2016) Those 26 are not the only critical success factors that affect software development projects, however, they appear at the top of many other studies like in Chiyangwa and Mnkandla (2017).…”
Section: Summary Of Critical Success Factorsmentioning
confidence: 99%
“…It has been found that the estimation of project management is less relevant to project competence (Mir & Pinnington, 2014). The Capability Maturity Model (CMM) was used by many organizations when the poor ICT project plan was considered to be the root cause of the project's failure (Kabir & Rusu, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%